Faktor-Faktor yang Berpengaruh Terhadap Keparahan Infeksi Dengue pada Anak: English - PUTU AYUNDA TRISNIA; SARASWATI LAKSMI DEWI; SRI MASYENI (Universitas Hang Tuah, 2025)
Dengue infection is one of the significant global health problems, especially in children. This paper aims to identify factors that affect the severity of dengue infection in the child population. The factors analysed included age, infection status, obesity, viral genome and Ns1 protein titers of dengue. Children who are younger and have an obese nutritional status tend to experience more severe symptoms. In addition, high NS1 titers, viral genomes, and secondary infections also contribute to a higher risk of infection. Detecting warning signs is important because it can be used as a predictor of more severe dengue infection.